What is wrong with gravity (and what we can do to fix it) - Cruz, Donniel (Animo Repository, 2021)
The College of Science Physics Department cordially invited the academic community to a lecture entitled What is wrong with gravity (and what we can do to fix it) by Mr. Donniel Cruz. Abstract: There is something wrong with gravity. General relativity (GR) had been historically known for its crazy predictions that turned out to be true. From the bending of light in the vicinity of massive objects, to the inescapable pull of black holes, and even to the undulations of spacetime itself in the form of gravitational waves. Einstein's brilliant idea is that space and time, together as space-time, can curve and bend due to matter and energy; and that this bending and curving is what we perceive as gravity. This idea has been verified and tested thousands of times since its conception more than a hundred years ago. But when it comes to the scale of galaxies, the predictions of GR fall short; the theory predicts a much weaker gravitational interaction than what astronomers observe with their telescopes. Physicists hypothesize the existence of Dark Matter to compensate for this apparent missing gravitational strength. But decades of search for what exactly this new matter is made of had proven to be unfruitful.